Proceso de Reclutamiento y Selección de Personal de la Empresa Cooproclem - Quinnacela Garzon, Judith Marisela (2018)
COOPROCLEM is the cooperative that offers the most work in the city of Babahoyo being the economic sustenance of thousands of families in the locality and its surroundings, as are the La Unión parish, La Lola, La Esmeralda, Los Beldacos and other localities of the Province of Los Ríos. This is how this production and marketing cooperative has gained recognition within the province and nationally for being one of the largest sources of employment that provides opportunities to work with professionals of the branch administrative and agricultural, as well as people who in most cases do not count with no type of study, more than with the experience acquired throughout his life in what are the labors of the field.